AT: Anthropology Today (John Wiley & Sons, Ltd, 2016)
Vol. 33, No. 4, Agustus 2017Edisi kali ini memuat beberapa tulisan. Di antaranya: The West’s Moral and Politial Crisis (hal. 1). Natural Hazards and Religion in New Orleans: coping strategies and interpretations (hal. 3). Taking Rumours Seriously: why organ thieves matter to malaria control (hal. 9). Ethical Practice and Techniques of the Self at a Yoga School in Southern India (hal. 13). Violins and Trowels for Palmyra: post-conflict heritage politics (hal. 18).